2008
DOI: 10.1016/s0140-6736(08)61113-7
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy of individuals on combination antiretroviral therapy in high-income countries: a collaborative analysis of 14 cohort studies

Abstract: Summary Background Combination antiretroviral therapy has led to significant increases in survival and quality of life, but at a population-level the effect on life expectancy is not well understood. Our objective was to compare changes in mortality and life expectancy among HIV-positive individuals on combination antiretroviral therapy. Methods The Antiretroviral Therapy Cohort Collaboration is a multinational collaboration of HIV cohort studies in Europe and North America. Patients were included in this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
503
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,423 publications
(521 citation statements)
references
References 42 publications
12
503
1
5
Order By: Relevance
“…Patients in our cohort were treated before the release of these guidelines and we observed the opposite trend of delayed treatment in older patients: the median CD4 cell count at the start of treatment was lower in older patients than in younger patients (176 vs. 200/µl, p = 0.017). It was previously shown that a lower CD4 cell nadir at the start of ART was a predictor for increased mortality [3,4,13,20]. Thus, our data demonstrate that older patients were in fact disadvantaged with regard to optimal care in the past, highlighting the need for improved care of older patients through earlier initiation of ART.…”
Section: Discussionsupporting
confidence: 52%
“…Patients in our cohort were treated before the release of these guidelines and we observed the opposite trend of delayed treatment in older patients: the median CD4 cell count at the start of treatment was lower in older patients than in younger patients (176 vs. 200/µl, p = 0.017). It was previously shown that a lower CD4 cell nadir at the start of ART was a predictor for increased mortality [3,4,13,20]. Thus, our data demonstrate that older patients were in fact disadvantaged with regard to optimal care in the past, highlighting the need for improved care of older patients through earlier initiation of ART.…”
Section: Discussionsupporting
confidence: 52%
“…In the era of antiretroviral therapy (ART), there have been striking decreases in acquired immune deficiency syndrome (AIDS)‐related mortality 1, 2, 3 and prolongation of life expectancy 4, 5, 6, 7 for people living with HIV infection (PLWH). With this, there has been a shift in distribution of causes of death toward non‐AIDS‐defining events (NADEs) 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Access to anti-retroviral therapy (ART) improved the life expectancies of people living with Human Immunodeficiency Virus (HIV) globally [1,2]. However, their medication adherence remains salient.…”
Section: Introductionmentioning
confidence: 99%